Test automation strategies for Unity-based mobile games - Ivashchenko, Yevhenii (National Technical University "Kharkiv Polytechnic Institute", 2025)
Mobile game development faces unique quality assurance challenges due to complex interactive content and rapid release cycles. This study examines test automation techniques for Unity-based mobile games, pointing out both benefits and problems. We examine third-party frameworks and Unity's integrated testing tools, discuss real-case implementations, and examine how automated testing might boost mobile game quality assurance productivity. The findings underscore the practical significance of tailored automation approaches in enhancing reliability and continuous delivery for Unity mobile games.
Keywords: unity; test automation; quality assurance; automated testing; mobile games